Synchro-Mining: the New Sight - Amosha, O.; Cherevatskyi, D.; Pivnyak, G.; Shashenko, O.; Borodai, L. (Економічний вісник Донбасу, 2019)
The analysis of Synchro-Mining alternatives, performed by the paper, has shown the multidimensionality being typical for the ideology and even controversy stipulating complexity of its understanding both by practices and by qualified scientists.
It has been substantiated that it is expedient to base the Synchro-Mining phenomenon on Mining interpretation by Merriam-Webster Dictionary version relying upon the existence primacy of a mining enterprise (i.e. a mine, quarry, open pit, well etc.): Mining exists irrespective of the mineral extraction until the enterprise is liquidated physically.
Thus, Synchro-Mining is diversification of the key activity of a mining enterprise performed in parallel with Mining whether it is coal or ore preparation, generation of electric energy and thermal energy, early Post-Mining measures, commercial extraction of methane, deep treatment of mine water, progress of circular economy etc. not only in the form of vertical integration of various businesses (i.e. hierarchical production method) but also in the form of heterarchies (i.e. network capitalism) or in the form of industrial parks. Виконаний у роботі з використанням методу кейсів аналіз варіантів побудови Synchro-Mining показав властиву самій ідеології багатоаспектність, а то й суперечливість, що обумовлює складність її сприйняття не тільки практиками, а й навіть підготовленими вченими.
Обґрунтовано, що в основу феномена Synchro-Mining раціонально покласти тлумачення Mining (Гірництва) у версії словника Merriam-Webster, заснованого на приматі існування гірничодобувного підприємства (шахти, рудника, кар'єру, свердловини тощо): Mining існує незалежно від видобутку корисних копалин до тих пір, поки фізично не ліквідовано саме підприємство.
Таким чином, Synchro-Mining – це диверсифікація основної діяльності гірничодобувного підприємства, яка проводиться синхронно з Mining, будь-то в напрямку збагачення вугілля або руди, виробництва й акумуляції електричної та теплової енергії, заздалегідь проведених заходів Post-Mining, комерційного видобутку метану, глибокого очищення шахтних вод, розвитку циркулярної економіки та ін., як у формі вертикальної інтеграції різнопрофільних бізнесів (ієрархічний спосіб виробництва), так і у вигляді гетерархій (мережевого капіталізму), чи індустріальних парків. Выполненный в работе с использованием метода кейсов анализ вариантов построения Synchro-Mining показал свойственную самой идеологии многоаспектность, а то и противоречивость, что обусловливает сложность ее восприятия не только практиками, но даже подготовленными учеными.
Обосновано, что в основу феномена Synchro-Mining рационально положить толкование Mining (Горное дело) в версии словаря Merriam-Webster, основанного на примате существования горнодобывающего предприятия (шахты, рудника, карьера, скважины и т.д.): Mining существует независимо от добычи полезных ископаемых до тех пор, пока физически не ликвидировано само предприятие.
Таким образом, Synchro-Mining – это диверсификация основной деятельности горнодобывающего предприятия, которая проводится синхронно с Mining, будь то в направлении обогащения угля или руды, производства и аккумуляции электрической и тепловой энергии, заранее проведенных мероприятий Post-Mining, коммерческой добычи метана, глубокой очистки шахтных вод, развития циркулярной экономики и др., как в форме вертикальной интеграции разнопрофильных бизнесов (иерархический способ производства), так и в виде гетерархий (сетевого капитализма), или индустриальных парков.